(untitled) (Malay Literature, 2021)
Historiographical works are an important source in tracing the early interactions between the Malays and Chinese, through the depiction of certain personages. Furthermore, the Malay society’s knowledge about China is presented by the writers through charming descriptions of Chinese customary practices, traditions and arts. At the same time, an assessment of the relationship between the Malays and Chinese, as presented in historiographical works, reveal many mythical elements whose existence requires explanation. This raises many questions concerning the existence of Chinese personages and Chinese presence in Malay historical writings, and to what the extent these accounts are true. This article will discuss these issues by examining selected historiographical works in Malay literature and related historical records. The discussion is based on an intercultural approach to Malay literature and its relevance to the present time.